The visionary artist - Lambert, Moira (Rhodes University, Faculty of Humanities, Department of Fine Art, 1980)
Reading and personal experiences have often drawn my attention to the exceptionally high incidence of despair, "nervous disorder", alcoholism, nihilism and even suicide, among modern artists. I would like in this work to look at the visionary, Blake, against the problem of 'breaking the sound-barrier' and against the background of disastrous attempts at this by modern artists.
Keywords: Blake, William, 1757-1827; Blake, William, 1757-1827 -- Symbolism